OPTIMIZATION OF THE METHOD OF OBTAINING PESTINE PP AND STUDYING ITS SPECIFIC ACTIVITY IN VITRO - S. E. Gostischeva; N. V. Abzaeva; D. A. Kovalev; D. G. Ponomarenko; Yu. V. Siritsa; E. L. Rakitina; E. N. Afanasyev; M. V. Kostuchenko (Инфекция и иммунитет, 2018)
The formation of immunity against infectious diseases is accompanied by an immunoallergic alteration of the organism, while the intensity of the allergic reaction is associated with the presence of specific immunity. Skin allergotesting is often used to determine the intensity of sensitization of the body. When determining the immunity of vaccines against the plague, previously an allergen was suggested as a pestin PP — a polypeptide polysaccharide complex of a plague microbe. The authors optimized the technique for obtaining the preparation of pestin with preservation of its chemical composition, high specificity and allergenic activity. It is known that a lack of allergic test in vivo is a high risk of formation of adverse reactions. A method for estimating adaptive antiplague immunity with the allergen pestin in antigen-specific cellular tests in vitro is proposed. The preparation of the allergen by a modified procedure was carried out by hydrolysis of the biomass of the vaccine strain of the plague microbe Yersinia pestis EV of the NIIEG line, followed by filtration and lyophilization of the precipitate. In the preparation obtained, the pH and the protein concentration were determined. To check the specificity, the samples were subjected to spectrophotometric and chromatographic analysis. To assess specific activity, blood samples of 17 people immunized with the plague live vaccine from the Yersinia pestis EV strain of the NIIEG line were used for epidemic indications. As a comparative control, a sterile isotonic sodium chloride solution was used. The contingent was examined before vaccination on days 7, 21 and 3 months after immunization by evaluating the expression intensity of basophils CD63. Biochemical analysis of the obtained by the modified procedure of the pestin and derivatives allowed to judge the qualitative composition, to show the absence of impurities of the protein nature, as well as to determine the carbohydrate profile. The use of the drug as an allergen to assess the formation of antiplague immunity in the vaccinated contingent confirmed its specificity. The obtained data showed the possibility and prospect of using the Pestin PP as a test allergen for the establishment of the reaction of activation of basophils in vitro.